PERUBAHAN POLA CURAH HUJAN DI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN (TAHUN 2003 - 2012) - Yani, Zulhijah Defitri; Edial, Helfia; Farida, Farida (STKIP PGRI Sumbar, 2013)
The research was based on a different pattern of rainfall in the Distric t XI Tarusan Koto. The result of this study reveals the magnitude of the average rainfall that occurred in District XI Tarusan Koto in the period 2003-2012 as well as changes in rainfall patterns.This research used descriptive quantitative method for processing of secondary data. Quantitative descriptive research is to conduct secondary data description of the data and then perform data analysis to obtain conclusions. This research area is Koto XI Tarusan, South Coastal District. The research data was taken from the station BMKG Regional Sicincin and PSDA West Sumatra province. Of all the data taken on average of 10 years from 2003 to 2012 from of three point of observation post located in Koto XI Tarusan, Nanggalo Tarusan, and Duku.The results showed that : 1) The average rainfall in the 2003-2012 observation period ranged from 2749.3 to 3136.3 mm / year and (2) the rainfall in the sub District Tarusan, equatorial rainfall pattern obtained with bimodal shape ( two peak rainfall ), where low rainfall occurred in January-June, while the high rainfall occurred in August-December. Of the three rainfall stations, there are no changes in rainfall patterns mean.